THE EFFECT OF WELFARE BENEFITS TOWARD EMPLOYEE PERFORMANCE AT PT. BANK PANIN, TBK IN MAKASSAR CITY - Nurlina, . (Advances in Social Sciences Research Journal, 2020)
This study aims to determine the effect of welfare benefits toward employee performance at PT. Bank Panin, Tbk in Makassar City. This research is a quantitative research. The population in this study were all employees at PT Bank Panin, Tbk in Makassar City, of 228 people. Then the sample is the author takes 20 percent of the population, of 46 people. Data collection methods are carried out by observation, documentation, and questionnaires. The data analysis technique used is a simple linear regression analysis for hypothesis testing. The results showed that providing welfare benefits to employees had a positive and significant effect on employee performance at PT. Bank Panin, Tbk in Makassar City.